Protein Considerations for Athletes With a Spinal Cord Injury - Flueck, Joelle Leonie; Parnell, Jill A. (Frontiers in Nutrition, 2021)
Athlete participation in the Paralympic games is steadily increasing; prompting research focused on the unique needs of this population. While the Paralympic Games includes a diversity of athletes, athletes with a spinal cord injury (PARA-SCI) represent a subgroup that requires specialized recommendations. Nutritional guidelines designed to optimize performance, in the context of the neurological impairments, are required. This narrative review summarizes the current literature regarding the importance of dietary protein for optimal health and performance. Factors with the potential to affect protein needs in PARA-SCI including loss of active muscle mass, reduced energy expenditure, and secondary complications are examined in detail. Furthermore, we analyze protein intakes in PARA-SCI from the available research to provide context around current practices and trends. In conclusion, we make the case that protein recommendations for able-bodied athletes may not be directly transferable to PARA-SCI. Consequently, PARA-SCI need their own guidelines to maximize performance and ensure long-term health.